2014
DOI: 10.1038/ncomms6705
|View full text |Cite
|
Sign up to set email alerts
|

The small-molecule BGP-15 protects against heart failure and atrial fibrillation in mice

Abstract: Heart failure (HF) and atrial fibrillation (AF) share common risk factors, frequently coexist and are associated with high mortality. Treatment of HF with AF represents a major unmet need. Here we show that a small molecule, BGP-15, improves cardiac function and reduces arrhythmic episodes in two independent mouse models, which progressively develop HF and AF. In these models, BGP-15 treatment is associated with increased phosphorylation of the insulin-like growth factor 1 receptor (IGF1R), which is depressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 71 publications
4
105
1
Order By: Relevance
“…For example, the heat-shock response is enhanced by increased levels of the molecular chaperone HSP72 (21,24,26,28,29), possibly mediated by Rac-1 signaling (31, 32). BGP-15 also decreases phospho-JNK (pJNK) and p38 stress signaling (21, 23) and increases AKT and IGFR1 protective signaling (23,25). Additionally, in models of stress and injury, BGP-15 has been shown to decrease cell stress by restoring normal mitochondrial function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the heat-shock response is enhanced by increased levels of the molecular chaperone HSP72 (21,24,26,28,29), possibly mediated by Rac-1 signaling (31, 32). BGP-15 also decreases phospho-JNK (pJNK) and p38 stress signaling (21, 23) and increases AKT and IGFR1 protective signaling (23,25). Additionally, in models of stress and injury, BGP-15 has been shown to decrease cell stress by restoring normal mitochondrial function.…”
mentioning
confidence: 99%
“…BGP-15 is a hydroxylamine derivative that has been shown to exert cyto-and neuroprotective effects in mammalian models of injury, stress, and disease (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). These improvements in cellular function have been correlated with the activation of several intracellular pathways.…”
mentioning
confidence: 99%
“…The HS response inducer BGP-15 has proven to efficiently reverse the noxious effects of HFD-induced obesity in the muscle and adipose tissue, by increasing the HS response [12]. BGP-15 improves cardiac function and reduces arrhythmic episodes in different mouse models that progressively develop heart failure and atrial fibrillation and can provide cytoprotection and normalization of cell signaling, which are often defective in the aged and diseased heart [287]. Therefore, if BGP-15 was developed to simulate the beneficial effects of exercise, it is plausible to suppose that exercise itself should present better (or the best) accomplishment.…”
Section: Physical Exercise Glutamine and Hs Response In Agingmentioning
confidence: 99%
“…Further supporting that insulin signalling is involved in membrane sensing of heat the protection of a small molecule, BGP-15 against heart failure and atrial fibrillation was associated with an increased phosphorylation of the insulin-like growth factor 1 receptor (IGF1R) (Sapra et al 2014). Since BGP-15 was also shown to be an HSP coinducer and its ability to activates stress signal transduction pathways by remodeling plasma membrane rafts (Gombos et al 2011).…”
Section: Igf1r Signallingmentioning
confidence: 99%
“…In atrial fibrillation susceptible animal model, depressed IGF1R in atrial samples is correlated with the increase ganglioside levels that reduces membrane fluidity and inhibits phosphorylation of IGF1R. In the presence of BGP-15, membrane fluidity is increased and ganglioside levels are reduced, therefore it is suggested that BGP15 attenuates ganglioside interaction to restore IGF1R signalling (Sapra et al 2014). Another report is the activation of IGF1R by sheer stress causing the downstream ERK 1/2 activation in an IGF1R dependent manner.…”
Section: Membrane Sensor Theorymentioning
confidence: 99%